Los juegos del lenguaje como estrategia creativa para la enseñanza de cuentos. Una investigación etnográfica referida a tres docentes de ciclo II pertenecientes a la Institución Educativa Distrital Altamira Sur Oriental de la ciudad de Bogotá - Fuquene Solorza, Johana (Universidad de La Salle. Facultad de Ciencias de la educación. Maestría en Docencia (incluye Maestría en Docencia - CESMAG)., 2017)
This paper aims to establish the language games function within teaching strategies to strengthen the stories writing on cycle II students from Altamira Sur Oriental Public School in Bogotá City. Additionally, it intends to describe didactics implemented by teachers to teach how to write stories, besides tends to ascertain the creativity level on three teachers practicums, whose purpose is students writing stories.